Relationship Between Cash Flow Volatility And Capital Structure (An Empirical Study on Banks Listed at Damascus Securities Exchange) - ديبه رشا; اياد حاتم; عفراء علي (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This research aims to test the impact of the volatilities in cash flows with their various net activities (operating, investing, and financing), in addition to Volatility in the Net cash flows on capital structure of banks listed in the Damascus Securities Exchange on. The research community consisted of 14 banks, during the time period from 2015 to 2022. Four independent variables were used؛ which are the Volatility of cash flows from activities (operating, investing, financing), in addition to the Volatility of Net cash flows, and its were measured according to the standard deviation. The capital structure was also measured through ratio of Total Assets/Equity, and a controlling variable was used, which is the size of the bank, as it was measured through the natural logarithm of total Assets. The E-view10 program was used, and three models (pooled regression model, fixed effects, and random effects) were compared through the F test and the Hausman test. Results showed that there is significant positive relationship between volatilities of financing cash flows and capital structure, were explanatory value of the model is 18,4%, and there is no statistically significant relationship between volatilities of net cash flows, and volatilities of operating and investing cash flows and the capital structure of private banks.